Off-Line Electrodes’ Effect On A Wenner And Wenner-Schlumberger Array Using Two-Dimensional Electrical Resistivity Tomography - Adejo, Mohammed Mustapha (2021)
Standard protocols employed for two-dimensional electrical resistivity tomography (2-D ERT) survey are designed with the assumption of collinear electrode pairs at each point of measurement. However, due to the presence of surface constraints associated with most of the survey areas, it is seldom possible to conduct resistivity surveys along a straight line. Therefore, 2-D ERT survey conducted on a surface constraint field requires shifting some electrodes off the survey line, which is in contrast to the underlying principle. Consequently, uncertainties might creep into the results. The purpose of this research is to ascertain the potential effect posed by electrodes offline on a 2-D resistivity data and develop a template to mitigate the effect. To this end, resistivity tomography using the most common arrays (Wenner and Wenner-Schlumberger) were conducted. For each array, data was acquired with all multi-electrodes inline, one offline, two offline, and three offline at stepwise distances, respectively. The results show that electrodes offline on a 2-D ERT survey have a significant effect on both arrays, especially when two or more electrodes are offline at a distance >½ the minimum electrode spacing “a”. Also, the quantitative assessment carried out using Pearson’s correlation coefficient (PCC), mean absolute error (MAE), and mean absolute percentage error (MAPE) further revealed the effect with low PCC (< 0.7). The percentage error is however, high (>18%) for Wenner-Schlumberger array model and low (<10%) for Wenner array model.